2011
DOI: 10.1016/j.cub.2011.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evidence for Ancient Asexuality in Timema Stick Insects

Abstract: Asexuality is rare in animals in spite of its apparent advantage relative to sexual reproduction, indicating that it must be associated with profound costs [1-9]. One expectation is that reproductive advantages gained by new asexual lineages will be quickly eroded over time [3, 5-7]. Ancient asexual taxa that have evolved and adapted without sex would be "scandalous" exceptions to this rule, but it is often difficult to exclude the possibility that putative asexuals deploy some form of "cryptic" sex, or have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(101 citation statements)
references
References 39 publications
3
97
1
Order By: Relevance
“…This hypothesis is consistent with reported evidence for shortlived apomictic lineages, for example, the derived fern genus Astrolepis [5], and the developmental feature changes required for the loss of sexuality in plants [3]. However, it is inconsistent with other studies that recover evidence for species rich lineages that lack any reported evidence for at least rare sexual events [6,7], and a recent study on the eudicot genus Oenothera, which shows "increasing diversification associated with loss of sexual recombination and segregation" [4]. This conflicting evidence questions 2 Journal of Botany our general understanding of the evolution of asexual reproduction, and the causes of its uneven distribution among animals and land plants.…”
Section: Introductioncontrasting
confidence: 54%
“…This hypothesis is consistent with reported evidence for shortlived apomictic lineages, for example, the derived fern genus Astrolepis [5], and the developmental feature changes required for the loss of sexuality in plants [3]. However, it is inconsistent with other studies that recover evidence for species rich lineages that lack any reported evidence for at least rare sexual events [6,7], and a recent study on the eudicot genus Oenothera, which shows "increasing diversification associated with loss of sexual recombination and segregation" [4]. This conflicting evidence questions 2 Journal of Botany our general understanding of the evolution of asexual reproduction, and the causes of its uneven distribution among animals and land plants.…”
Section: Introductioncontrasting
confidence: 54%
“…Animals that are incapable of adapting to changes in their environment are arguably doomed to extinction if major changes occur and would represent evolutionary dead ends [Matthey, 1941;White, 1970White, , 1973. Nevertheless, the ones studied by Matthey and White are currently doing well: some have persisted for hundreds of millions of years, prompting Maynard Smith to label bdelloid rotifers 'evolutionary scandals' [Schön et al, 2009; see also Schwander et al, 2011], or at least tens of thousands of years . Many modes of parthenogenesis allow the retention of new mutations and genetic variation.…”
Section: Meiosis In Parthenogenetic Polyploid Animalsmentioning
confidence: 99%
“…Finally, the development of functional males may indicate that lineages presumed to be asexual have some low level of cryptic sex. However, although formally demonstrating the lack of sexual reproduction in a lineage is challenging [53], this explanation is unlikely in groups that display the genomic signatures of asexuality, such as Timema [25,30,54], and is difficult to reconcile with decay of sexual traits in females, reported in cases with functional males [37] (this study).…”
Section: Discussionmentioning
confidence: 92%
“…For each of the five sexual species, we conducted 109 -211 trials (30-98 for each of the three female groups), for a total of 751 two-choice trials, with different individuals used Table 1. Independently derived asexual Timema lineages and their sexual sister species, ranked by increasing upper age estimates (age estimates from [25], based on intra-and interspecific molecular divergences). The asexual lineages in bold were included in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation